Desenvolvimento de sensor para quantificação do fluxo de massa de fertilizantes sólidos - Becker, Rafael Sobroza (2020)
This study assumes that the insertion of sensors capable of instantaneous measurement of the mass flow of fertilizers, after its release by the feeder, can assist in the monitoring of the rates applied in each seeding line, through the measurement of instantaneous data, so that it can serve as a correction base for the controllers that equip the automated systems. With this, the verification and adjustments allow greater efficiency in the distribution of fertilizers, causing an increase in profitability. Therefore, the objective comprises the develop a system with a microwave sensor, to quantify the mass flow of solid fertilizers, depending on the granulometry of the fertilizer and the driving speeds. The study was conducted at the Agricultural Machinery Research and Development Laboratory (LASERG / UFSM). A test bench with fertilizer feeders was used, coupled with a helical feeder (endless), with fertilizer discharge by transverse overflow. Its activation was performed by an electric motor of 0.735 kW. For the alteration and the control of the rotation, the bench had a frequency inverter and a data measurement system. The fertilizers used were of the mineral type classified as granular mixture, mixture of granules and, bran mixture, for that some physical properties were determined. The application rate g min-1 was performed by measuring the mass of fertilizers collected in an interval of 30 seconds, after stabilizing the system. A concept was assembled with electronic components to automate the mass flow estimation, so that it was validated and calibrated through static tests, performed by means of manual measurement. The experiment was arranged in a completely randomized design (DIC), in a three-factor arrangement (measurement method, type of fertilizer and drive rotation), with 5 repetitions. It was observed that the regulation of the frequency inverter is directly proportional to the dosing speed. With this, the conversion of the desired speed in the feeder to the frequency used in the inverter can be calculated by a linear equation with a determination coefficient of 99.99 %. The sensor allowed the identification of the increase in the speed of the particles and, as a result, it is possible to estimate the application rate, which is directly proportional to the drive speed. The measurement methods did not differ when using granular mixture and granule mixture type fertilizers, showing that the use of a sensor is valid to measure the mass flow of the fertilizers. For the mash mixture, the sensor underestimated the application rate by 21.56 %, confirming its difficulty in accurately estimating the densest materials with the smallest particle sizes.